Brian Blount as Eventful Preacher - Long, Thomas G. (Interpretation, 2025)
As an academically trained biblical scholar and as one formed in the Black Church tradition, Brian Blount combines in his preaching attention to the rhetorical power of biblical texts characteristic of recent trends in philosophical hermeneutics with a social hermeneutic born out of the experience of the Black Church. The result is preaching that is eventful in impact, apocalyptic in theological outlook, and interventionist in rhetorical strategy.